Genome editing weds CRISPR: what is in it for phytoremediation? - Basharat, Zarrin (2018)
The arrival of sequence-specific endonucleases that allow genome editing has shaken the pillars of basic and applied plant biology. Clustered regularly interspaced palindromic repeats (CRISPR) is a revolutionary genome-engineering tool that enables the enhancement of targeted traits in plants. Numerous plants, including energy crops, known for their potential to tolerate, immobilize, and stabilize inorganic and organic pollutants, have already been edited using different CRISPR systems. Moreover, a large array of genes responsible for increased metal tolerance, metal uptake and hyperaccumulation have already been identified. Thus, the CRISPR-mediated genome reprogramming of plants, including its use in gene expression regulation through transcriptional repression or activation (CRISPRi and CRISPRa), could be of paramount importance for phytoremediation. The simplicity, inexpensiveness, and capabilities of this gene editing technique could soon be used to enhance plants and bacteria involved in phytotechnologies, such as phystabilization, phytoextraction, phytomining, phytovolatilization, and bio-energy generation. In this brief viewpoint piece, we posit some of the potential benefits of CRISPR for phytoremediation.